Abscisic acid affects expression of citrus FT homologs upon floral induction by low temperature in Satsuma mandarin (Citrus unshiu Marc.). (22nd November 2017) - Endo, Tomoko; Shimada, Takehiko; Nakata, Yumi; Fujii, Hiroshi; Matsumoto, Hikaru; Nakajima, Naoko; Ikoma, Yoshinori; Omura, Mitsuo
Abstract: After a long juvenile period, citrus trees undergo seasonal flowering cycles. Under natural conditions, citrus flowering is regulated mainly by low ambient temperatures around 15–20 °C and water deficit stress. Recent studies have revealed that fluctuations in the expression of citrus homologs of FLOWERING LOCUS T ( FT, encoding a flowering integrator) are correlated with their presumed role as flower-promoting signals. Previous ectopic expression analyses have demonstrated the flower-promoting function of citrus FT homologs. In this study, we examined whether abscisic acid (ABA) affects the expression of FT homologs and the flowering induced by low ambient temperatures. Application of exogenous ABA to potted Satsuma mandarin ( Citrus unshiu Marc.) trees resulted in transient accumulation of citrus FT homolog transcripts. The promoter of one citrus FT homolog, CiFT3, was active in transgenic A. thaliana (Arabidopsis thaliana) and responded to exogenous and endogenous ABA. CiFT3 is preferentially expressed in shoots, and its expression was affected by flower-inductive treatments. Endogenous ABA accumulated in mandarin shoots during the floral induction period at 15 °C and under field conditions. The accumulation of ABA was correlated with the accumulation of FT homolog transcripts and flowering intensity. It was consistent with changes in the expression of genes related to ABA metabolism. The abundance of carotenoid precursors that serve as substrates for ABA biosynthesis decreased in leaves during the accumulation of ABA. Our data indicate that ABA and carotenoid precursors in leaves influence the flowering of mandarin trees induced by low temperature.